Anchoring a Leviathan: How the Nuclear Membrane Tethers the Genome - Czapiewski, Rafal; Robson, Michael I.; Schirmer, Eric C. (Frontiers in Genetics, 2016)
It is well established that the nuclear envelope has many distinct direct connections to chromatin that contribute to genome organization. The functional consequences of genome organization on gene regulation are less clear. Even less understood is how interactions of lamins and nuclear envelope transmembrane proteins (NETs) with chromatin can produce anchoring tethers that can withstand the physical forces of and on the genome. Chromosomes are the largest molecules in the cell, making megadalton protein structures like the nuclear pore complexes and ribosomes seem small by comparison. Thus to withstand strong forces from chromosome dynamics an anchoring tether is likely to be much more complex than a single protein-protein or protein-DNA interaction. Here we will briefly review known NE-genome interactions that likely contribute to spatial genome organization, postulate in the context of experimental data how these anchoring tethers contribute to gene regulation, and posit several hypotheses for the physical nature of these tethers that need to be investigated experimentally. Significantly, disruption of these anchoring tethers and the subsequent consequences for gene regulation could explain how mutations in nuclear envelope proteins cause diseases ranging from muscular dystrophy to lipodystrophy to premature ageing progeroid syndromes. The two favored hypotheses for nuclear envelope protein involvement in disease are 1) weakening nuclear and cellular mechanical stability, and 2) disrupting genome organization and gene regulation. Considerable experimental support has been obtained for both. The integration of both mechanical and gene expression defects in the disruption of anchoring tethers could provide a unifying hypothesis consistent with both.